2020
DOI: 10.1038/s41598-020-74575-y
|View full text |Cite
|
Sign up to set email alerts
|

Probing coordinated co-culture cancer related motility through differential micro-compartmentalized elastic substrates

Abstract: Cell development and behavior are driven by internal genetic programming, but the external microenvironment is increasingly recognized as a significant factor in cell differentiation, migration, and in the case of cancer, metastatic progression. Yet it remains unclear how the microenvironment influences cell processes, especially when examining cell motility. One factor that affects cell motility is cell mechanics, which is known to be related to substrate stiffness. Examining how cells interact with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…From the migration distance measured in this study, cells moved at the highest speed in S2 gels with uniform stiffness (Figure 9a), consistent with a previous finding. [53] It has been demonstrated that cell migration through the ECM is accompanied by changes in ECM structure. [54,55] As the stiffness of gels increase, more cellular work is required to cause matrix displacement, which entails higher energetic costs.…”
Section: Discussionmentioning
confidence: 99%
“…From the migration distance measured in this study, cells moved at the highest speed in S2 gels with uniform stiffness (Figure 9a), consistent with a previous finding. [53] It has been demonstrated that cell migration through the ECM is accompanied by changes in ECM structure. [54,55] As the stiffness of gels increase, more cellular work is required to cause matrix displacement, which entails higher energetic costs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, with the aim to perform a validation of the sensitivity of the measurement technique, we measured the strain drop of untreated 143B cells in comparison to 143B cells previously treated with glutaraldehyde (GA) (3% in PBS) [ 15 , 48 , 49 ] to make the cells stiffer than the control cells by creating chemical bonds between the cell and the substrate [ 50 ], or with cytochalasin-D (CD) (0.5 μg/mL in DMSO) to inhibit the assembly of actin filaments, reducing the cells’ ability to withstand stress [ 51 ] when plated on 5 kPa substrates. GA and CD treatments lasted 20 min and 15 min before the beginning of experimental testing, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted here that PDMS surface is highly hydrophobic [79], thus the ability of cells to adhere to this substrate is usually reduced. To overcome this problem, the PDMS substrates are usually modified, e.g., by coating with ECM proteins [80][81][82][83]. However, the spreading of cells on unmodified PDMS is possible for some cells [75,84], most likely due to the presence of serum proteins in the culture medium, serving as an adhesion matrix.…”
Section: Growth Of Cellsmentioning
confidence: 99%